2023
DOI: 10.1590/1806-9282.20220415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body composition and PBRM1 mutations in clear cell renal cell carcinoma: a propensity score matching analysis

Abstract: SUMMARY OBJECTIVE: This study aimed to examine the relationship between body muscle and adipose tissue composition in clear cell renal cell carcinoma patients with PBRM1 gene mutation. METHODS: Cancer Genome Atlas Kidney clear cell renal cell carcinoma and Clinical Proteomic Tumor Analysis Consortium clear cell renal cell carcinoma collections were retrieved from the Cancer Imaging Archive. A total of 291 clear cell renal cell carcinoma patients were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They 2 concluded that larger, preferably prospective, studies were needed to confirm and update their findings. Recently, in 2023, Demirel and Dilek 3 published, a study entitled “Relationship between body composition and PBRM1 mutations in clear cell renal cell carcinoma: a propensity score matching analysis” in the Journal of the Brazilian Medical Association 3 , in which they retrospectively examined the relationship between body muscle and adipose tissue composition in clear cell renal cell carcinoma patients with polybromo-1 protein (PBRM1) 4 gene mutation 3 . The study 3 concluded that normal attenuation muscle area is greater in patients with PBMR1 mutation, even after propensity score matching 3 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They 2 concluded that larger, preferably prospective, studies were needed to confirm and update their findings. Recently, in 2023, Demirel and Dilek 3 published, a study entitled “Relationship between body composition and PBRM1 mutations in clear cell renal cell carcinoma: a propensity score matching analysis” in the Journal of the Brazilian Medical Association 3 , in which they retrospectively examined the relationship between body muscle and adipose tissue composition in clear cell renal cell carcinoma patients with polybromo-1 protein (PBRM1) 4 gene mutation 3 . The study 3 concluded that normal attenuation muscle area is greater in patients with PBMR1 mutation, even after propensity score matching 3 .…”
mentioning
confidence: 99%
“…The study 3 concluded that normal attenuation muscle area is greater in patients with PBMR1 mutation, even after propensity score matching 3 . According to the authors, body composition plays a critical role in understanding the complex effect of PBRM1 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation